The future of the EU collaborative economy: using scenarios to explore future implications for employment - Joint Research Centre, Ispra; Bock, Anne-Katrin; Figueiredo do Nascimento, Susana; Szczepanikova, Alice (Luxembourg, 2016)
"The rapid growth of the collaborative economy has fuelled a discussion about its potential benefits and challenges. Moving the debate towards longer-term considerations the scenario-based JRC foresight project explores the possible future developments of the EU collaborative economy towards 2030. Results for platformmediated labour markets indicate several issues in relation to social protection of workers, data and reputation, and education and lifelong learning that need to be tackled irrespective of the future direction the EU will take. Furthermore, the potential for public service provision and social innovation should be actively explored."